Implementasi Bimbingan Rohani Islam melalui Doa dan Motivasi di RSUD Jati Padang - Ihfalia Irfana; Mei Handayani; Naila Alyssa; Sugiharto Sugiharto (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Islamic spiritual guidance is a form of spiritual service provided to hospitalized patients to support their psychological and spiritual needs during treatment. This activity was conducted at RSUD Jati Padang through prayer, motivation, spiritual assistance, and mental reinforcement for patients. The purpose of this activity was to improve inner peace, recovery motivation, and patients’ attitudes of patience and trust in Allah while facing illness. The methods used were direct observation and spiritual assistance during the treatment process. The results showed that Islamic spiritual guidance had a positive impact on patients’ psychological conditions, including reduced anxiety, increased inner peace, stronger motivation to recover, and improved quality of worship. In addition, patients’ families also benefited from emotional support and a greater sense of calm while accompanying their relatives. Therefore, Islamic spiritual guidance plays an important role in supporting patients’ holistic healing process.